Pendekatan Lintas-Budaya untuk Penyempurnaan Kurikulum di SMK Plus Bina Nusantara Mandiri Pariaman - Zen, Mustafa (AT-TA'LIM, 2014)
Diversity in the context of curriculum planning (students’ social, cultural, political affiliation and economic, does not only have a direct influence to teachers’ ability in carrying out the curriculum, but also school capacity to provide learning experience for the learners, as well as students’ ability to achieve optimum results.  In practice, however, curriculum planners often neglect this diversity.  Teachers with their authorized capacity feel ‘safe’ to be non-active in which they are not supposed to accommodate those diversities.  Neither they are to be involved in determining the philosophical views, theories, vision, documentary development, socialization and curriculum implementation, nor to work on standardized regulations that have been nationally and universally stated.  This paper is aimed at sharing the information dealing with appropriate approach that has to be done to accommodate the diversity of social, cultural, political affiliation and economic with the standard national curriculum toward the accomplishment of new curriculum in Vocational Bina Nusantara Mandiri School Pariaman.  Data were collected through field survey, observation, and interview with teachers as well as school community who contributed to curriculum development.Copyright © 2014 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v21i1.75